Daredevil by mark waid (2011), volume 6 ebook - Waid, Mark (Daredevil by Mark Waid (2011), 2014)
Collects Daredevil #28-30, Indestructible Hulk #9-10. There was one man young Daredevil feared and now Matt Murdock is representing him in court. The minor demons of Matt Murdock's past lead to some Daredevil sized present problems.